Terapi Storytelling Berpengaruh Terhadap Penurunan Kecemasan Anak Usia Pra-Sekolah Saat Menjalani Hospitalisasi Di Rumah Sakit: Storytelling Therapy Effects on Reducing Anxiety of Pre-School Age Children While Hospitalization in Hospital - Ihza Ramadhan, M. Rizky (Dohara POAJ, 2022)
Introduction: Anxiety is the impact of hospitalization experienced by children because they face stressors in the hospital environment. Forms of anxiety that arise such as restless children, fussy children, and crying, the condition certainly requires a folded strategy so that hospitalized preschoolers can receive programmed medical or nursing measures. One strategy that can be applied is storytelling therapy. Methods: The study used an experimental method involving 25 preschool child respondents. Results: T-Test statistical test results obtained significant numbers or probability values ​​(0.000) much lower standards significantly than 0.05 or (p < ) which means there is a significant difference in pre-school anxiety between before and after being given storytelling therapy. Discussion: Researchers concluded that there was an influence on the level of anxiety of childhood hospitalization before and after storytelling therapy.